2014
DOI: 10.1021/mp500316h
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Fatty Acid Amide Hydrolase with [18F]DOPP in Nonhuman Primates

Abstract: Fatty acid amide hydrolase (FAAH) regulates endocannabinoid signaling. [11C]CURB, an irreversibly binding FAAH inhibitor, has been developed for clinical research imaging with PET. However, no fluorine-18 labeled radiotracer for FAAH has yet advanced to human studies. [18F]DOPP ([18F]3-(4,5-dihydrooxazol-2-yl)phenyl (5-fluoropentyl)carbamate) has been identified as a promising 18F-labeled analogue based on rodent studies. The goal of this work is to evaluate [18F]DOPP in nonhuman primates to support its clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…It was found that a linear N -alkyl substituent leads to increased potency over cyclic isomers and that the presence of a dihydrooxazole confers faster and greater brain uptake with lower nonspecific binding. These insights lead directly to the design of two fluorine-18 labeled FAAH radiotracers: [ 18 F]DOPP 75,76 and [ 18 F]FCHC. 77 Both show greater brain uptake in vivo and sensitivity to FAAH activity in vitro than [ 11 C]CURB.…”
Section: [11c]co2-fixationmentioning
confidence: 99%
“…It was found that a linear N -alkyl substituent leads to increased potency over cyclic isomers and that the presence of a dihydrooxazole confers faster and greater brain uptake with lower nonspecific binding. These insights lead directly to the design of two fluorine-18 labeled FAAH radiotracers: [ 18 F]DOPP 75,76 and [ 18 F]FCHC. 77 Both show greater brain uptake in vivo and sensitivity to FAAH activity in vitro than [ 11 C]CURB.…”
Section: [11c]co2-fixationmentioning
confidence: 99%
“…8). 146,198,200,201,205 The radiofluorination reaction was carried out using the purified (distilled) fluorine-18 labelled building block, but also successful one-pot three step reactions including [ 18 F]fluorination and deprotection of the amine have been reported. In most syntheses, the carbamate formation was carried out at room temperature without additives.…”
Section: Fluorine-18 Labelled Alkyl Aminesmentioning
confidence: 99%
“…One-pot reaction at 80 1C with 2-[ 18 F]fluoroethyl azide-derived [ 18 F]fluoroethylamine under basic conditions (TEA) gave GABA A tracer 277 in 46% decay-corrected radiochemical yield (calculated from 2-[ 18 F]fluoroethyl azide). 205 Since 2010 the synthesis of two fluorine-18 labelled urea derivatives has been reported. In the procedure described by Majo et al, the potential PET ligand for mTOR 278 was synthesised from an amine precursor, which was pre-treated with trisphosgene and TEA in dichloromethane.…”
Section: Fluorine-18 Labelled Alkyl Aminesmentioning
confidence: 99%
“…Several FAAH inhibitors, classified as urea, carbamate, and keto-heterocycle derivatives, have been developed (Seierstad and Breitenbucher, 2008) and progressed to clinical trials to treat inflammatory pain, cannabis dependence, and schizophrenia (Kathuria et al, 2003;Li et al, 2012). Subsequently, to further understand the function of FAAH and to research JPET # 263772 drug kinetics in vivo, several positron emission tomography (PET) tracers for FAAH were synthesized based on the inhibitors (Shimoda et al, 2016;Kumata et al, 2015;Shimoda et al, 2015;Rotstein et al, 2014;Wilson et al, 2011) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%